Changes in the Mechanism of the Fenton Reaction - Mordechai L. Kremer (Reactions)
The kinetics of modified versions of the model of the Fenton reaction have been investigated. In these versions, radicals are produced by splitting FeO2+ (dissociation product of Fe2+ ozonide Fe2+O3) into Fe3+ and OH. The analysis shows that the revised models have the same shortcomings as the corresponding models of Haber and Weiss and of Barb et al. A nonradical model, based on an intact FeO2+ as an intermediate, accounted satisfactorily for the kinetics of the reaction under the same conditions. The amphoteric nature of FeO2+ to form FeOH3+ and HOFeO+ in reactions with H+ and OH−, respectively, extends its activity to a wide range of pH values.